Anopheles gambiae TEP1 forms a complex with the coiled-coil domain of LRIM1/APL1C following a conformational change in the thioester domain - Williams, Marni; Contet, Alicia; Hou, Chun-Feng David; Levashina, Elena A.; Baxter, Richard H. G. (PloS one, 2019)
The complement-like protein thioester-containing protein 1 (TEP1) is a key factor in the immune response of the malaria vector Anopheles gambiae to pathogens. Multiple allelic variants of TEP1 have been identified in laboratory strains and in the field, and are correlated with distinct immunophenotypes. TEP1 is tightly regulated by conformational changes induced by cleavage in a protease-sensitive region. Cleaved TEP1 forms exhibit significant variation in stability from hours to days at room temperature. In particular, the refractory allele TEP1*R1 is significantly more stable than the susceptible allele TEP1*S1. This raises the question of whether the stability of cleaved TEP1 is linked to allelic variation and varying immunophenotypes. We have analyzed the stability of the cleaved form of additional TEP1 alleles and constructs. We show that stability is correlated with allelic variation within two specific loops in direct proximity to the thioester bond. The variable loops are part of an interface between the TED and MG8 domains of TEP1 that protect the thioester from hydrolysis. Engineering specific disulfide bonds to prevent separation of the TED-MG8 interface stabilizes the cleaved form of TEP1 for months at room temperature. Cleaved TEP1 forms a soluble complex with a heterodimer of two leucine-rich repeat proteins, LRIM1 and APL1C, and precipitates in the absence of this complex. The molecular structure and oligomeric state of the TEP1/LRIM1/APL1C complex is unclear. The C-terminal coiled-coil domain of the LRIM1/APL1C complex is sufficient to stabilize the cleaved form of TEP1 in solution but cleaved forms of disulfide-stabilized TEP1 do not interact with LRIM1/APL1C. This implies that formation of the TEP1cut/LRIM1/APL1C complex is related to the conformational change that induces the precipitation of cleaved TEP1.